2018
DOI: 10.2174/1381612824666180829103355
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Formulas and Renal Fibrosis: An Overview

Abstract: All forms of chronic kidney disease (CKD) eventually lead to renal fibrosis irrespective of its origin. It is generally characterized by an excessive accumulation and deposition of extracellular matrix (ECM) and to date, no ideal treatment has been established. Bian-Zheng-Lun-Zhi (syndrome differentiation and treatment), a classic feature of traditional Chinese Medicine (TCM), is a unique method used to diagnose and treat the pathology of a disease. Zheng (syndrome) is used to demonstrate the nature of a disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…e therapeutic options for IUA are limited. However, several herbal medicines have been used to attenuate the generation of fibrotic tissue [30], especially in relation to hepatic [31], pulmonary [32], and renal [33] fibrosis. Evidence-Based Complementary and Alternative Medicine 7…”
Section: Discussionmentioning
confidence: 99%
“…e therapeutic options for IUA are limited. However, several herbal medicines have been used to attenuate the generation of fibrotic tissue [30], especially in relation to hepatic [31], pulmonary [32], and renal [33] fibrosis. Evidence-Based Complementary and Alternative Medicine 7…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kuo-Chin Huang, CKD patients treated with TCM exhibited an increased long-term survival rate. Shen et al (2018) reported that CHM formulas combine different herbal compounds to increase or promote therapeutic effectiveness, minimize toxicity and side effects, and optimize the therapeutic effects of each component, providing a safe and effective therapy for renal fibrosis. Therefore, the current study does not support that CHM therapy for gout can increase the risk of developing CKD.…”
Section: Discussionmentioning
confidence: 99%
“…TCM posits that disease of the body arises from an imbalance within the body and between the body and the nature, leading to an alteration in the entire body system [26]. In the practice of TCM, it is generally considered that multiple herbal medications are more effective than a single herbal agent, and in this way, the TCM formula could increase or promote therapeutic effectiveness and minimize toxicity and side effects [27].…”
Section: Discussionmentioning
confidence: 99%